The Effects of Green Product Knowledge, Perceived Price and Government Policy on Green Purchase Intention in Buying Hybrid Motor Vehicles - Lia Suprihartini; Dedi Herdiansyah; Meizi Fahrizal (Enrichment : Journal of Management, 2022)
The background of this research is to explore more deeply environmentally friendly motorcycle products with the Hybrid type, seek information about how the public as consumers understand environmentally friendly motorized vehicle products, find out how their perception of the price of environmentally friendly products is, and find out how the government has given efforts to encourage the public in the purchase and use of environmentally friendly motorcycles. Of course, before entering the stage of a battery-based or 100% electric vehicle, you should first step into the hybrid vehicle phase while preparing for the use of an electric motor in its entirety or a pure manner. The data analysis methodology used by the researchers is a qualitative method using the SPSS Version 22 program involving 100 respondents. Sampling was carried out by researchers using the Accidental Sampling technique. The results showed that the Green Product Knowledge variable significantly affected the Green Purchase Intention variable. In contrast, the Perceived Price variable had no significant effect on the Green Purchase Intention variable. Then, the Government Policy variable also significantly affects the Green Purchase Intention variable. Finally, the Green Product Knowledge, Perceived Price, and Government Policy variables were found to have a simultaneous effect on the Green Purchase Intention variable.